Teacher Performance and Multitasking Challenges in Indonesia - Anselmus Yata Mones; Casimiro Relvas Amaral (Universitas Pendidikan Ganesha, 2025)
Teacher performance is a crucial factor in ensuring the quality of education in Indonesia, but it is often affected by the increasing demands to complete many tasks simultaneously, This research aims to analyze the dual roles of teachers that affect their performance effectiveness in the context of implementing the Merdeka Curriculum. The method used in this study is qualitative. The population for this research includes all secondary school-level teachers in the three districts. Data was collected using several methods, including interviews, documents, and observation. Data obtained from interviews, observations, and document reviews were analyzed qualitatively using thematic analysis techniques. The findings indicate that excessive multitasking leads to reduced preparation time, increased work stress, and decreased focus on core teaching tasks. However, some teachers develop adaptive strategies, such as time management techniques and collaborative task division, to maintain performance. This research suggests policy adjustments to balance task distribution, reduce non-teaching workload, and provide professional development that enhances resilience in multitasking. This finding offers practical implications for improving teacher productivity and maintaining the quality of education in Indonesia.